The microtubule targeting agents eribulin and paclitaxel activate similar signaling pathways and induce cell death predominantly in a caspase-independent manner. Issue 4 (16th February 2020) - Hüsemann, Lisa C.; Reese, Alina; Radine, Claudia; Piekorz, Roland P.; Budach, Wilfried; Sohn, Dennis; Jänicke, Reiner U.
ABSTRACT: Microtubule-targeting agents (MTAs) are the most effective chemotherapeutics used in cancer therapy to date, but their clinical use is often hampered by the acquisition of resistance. Thereby, elucidation of the molecular signaling pathways activated by novel FDA-approved MTAs such as eribulin is important for future therapeutic applications. In contrast to several reports, we show here that regardless of the presence of caspase-3, clinically relevant concentrations of eribulin and the classical MTA paclitaxel predominantly induce caspase-independent cell death in MCF-7 breast carcinoma cells. On the molecular level, several key proteins involved in apoptosis such as p53, Plk1, caspase-2, and Bim as well as the two MAPKs ERK and JNK were activated by both compounds to a similar extent. However, none of them proved to be important for eribulin- and paclitaxel-induced cytotoxicity, as their siRNA-mediated knockdown or inactivation by small molecule inhibitors did not alter cell death rates. In contrast, knockdown of the anti-apoptotic Bcl-2 protein, which becomes heavily phosphorylated at Ser70 during MTA treatment, resulted surprisingly in a reduction of MTA-mediated cell death. This phenomenon can be most likely explained by our observation that the absence of Bcl-2 slowed down cell cycle progression resulting in fewer cells entering mitosis, thereby delaying the mitotic capability of these MTAs to induce cell death. Taken together, although eribulin and paclitaxel disturb the mitotic spindle differently, they exhibit no functional differences in downstream molecular cell death signaling in MCF-7 breast cancer cells.